PDPN is a prognostic biomarker and correlated with immune infiltrating in gastric cancer. Issue 19 (May 2020) - Hu, Liya; Zhang, Peng; Sun, Wei; Zhou, Lei; Chu, Qian; Chen, Yuan
Abstract : Abstract: Studies of PDPN in cancers have focused on the interactions with palates through the binding with CECL-2 which mainly express on palates and immune cells, while little is known on its interactions with immune cells. PDPN expression in cancers was analyzed through Oncomine, GEPIA, and TIMER database. Prognostic value (HR, P value from log-rank test) was evaluated through Kaplan–Meier plotter and OncoLnc database. The correlations between PDPN and the infiltrating levels of immune cells in different cancers, and diverse immune markers in gastric cancer were investigated through TIMER database. High PDPN expression predicted poor overall survival (OS) and post-progression survival (PPS) particularly in gastric cancer (OS P  = .0089; PPS P  = .00085), especially among patients with Her-2 (+) and lymph node metastasis. In addition, PDPN was positively correlated with infiltrating levels of immune cells, other than B cells in gastric cancer. However, PDPN showed more correlations with immune markers of M2 type TAM (CD163, VSIG4, MS4A4A) and T cell exhaustion (TIM-3, TOX, and GZMB). These findings all suggest that high PDPN predicts poor survival outcomes, especially for Her-2 (+) gastric cancer patients. Though inducing M2 type TAM and T cell exhaustion, high PDPN can predict high levels of various immune cells infiltration in STAD. Those correlations may bring new ideas to immunology treatment for gastric cancer patients who do not benefit from the existing immune checkpoint inhibitors. Abstract : Supplemental Digital Content is available in the text